Corporate Governance and Capital Structure Dynamics: A Case of Nepalese Insurance Companies - Pandey, Bibek Raj; Ram, Devendra Kumar; Mandal, Babby; Sah, Puja (Nepalese Journal of Business, 2025)
The study examines the impact of corporate governance on capital structure dynamics in Nepalese insurance companies. Total debt to equity and total debt to assets are the dependent variables. The selected independent variables are board size, independent director, audit committee, institutional ownership, female director and board meetings. The study is based on secondary data of 10 commercial banks with 100 observations for the study period from 2013/14-2022/23. The data were collected from Bank Supervision Report published by Nepal Rastra Bank (NRB), Ministry of Finance (MoF) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance on capital structure dynamics in Nepalese insurance company. The study showed that board size has a negative relationship with total debt to equity and total debt to assets. It means that increase in board size leads to decrease in total debt to equity and total debt to assets. Similarly, female director has a negative relationship with total debt to equity and total debt to assets. It means that increase in the number of female directors leads to decrease in total debt to equity and total debt to assets. Further, independent directors have a positive relationship with total debt to equity and total debt to assets. It means that increase in number of independent directors leads to increase in total debt to equity and total debt to assets. Moreover, board meeting has a positive relationship with total debt to equity and total debt to assets. It means that increase in the number of board meeting leads to increase in total debt to equity and total debt to assets. Similarly, the results show that audit committee has a positive relationship with total debt to equity and total debt to assets indicating that increase in audit committee leads to increase in total debt to equity and total debt to assets. In addition, institutional ownership has a positive relationship with in total debt to equity and total debt to assets. It means that increase in institutional ownership leads to increase in in total debt to equity and total debt to assets.